REFLEXII CU PRIVIRE LA TRECEREA DE LA METODE DE PREDARE TRADIȚIONALE LA CELE INOVATIVE - Mironov, Svetlana (CEP USM, 2022)
The Moldovan higher education system is exposed to transformations under the influence of factors of various etiologies. The demographic crisis, the exodus of the population and the constant decrease in the number of students impose on the universities the condition to be competitive. Increasing the competitiveness of universities can be achieved by increasing the quality of the student training process, which requires the transition from traditional teaching methods to innovative ones based on active student-centered learning. The pandemic situation, in turn, has created conditions for the transition to distance learning methods and the provision of online courses. The study conducted within the Erasmus + Higher Education Reform Experts in Moldova (HERE) project showed that teaching and learning methods determine the student's appreciation and interest in higher education. Last but not least, in order to identify teaching methods that will correlate professional skills with the needs of the labor market, it is necessary to know the "student profile of today" which differs significantly from previous generations of students. The aim of the transition to innovative teaching methods is to train and develop the skills that students need to acquire upon graduation and that will give graduates a better chance of entering the labor market.
Keywords: teaching methods; university; academic environment